PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DENGAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK DI SDN MUNJUK SAMPURNA - Heni Saputri (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2024)
Abstract The learning of Islamic Education and Character Building (PAI) requires learning innovation that begins with a student-centered learning approach. One of the innovations in the PAI learning model that was implemented in the new academic year 2023/2024 at di SDN Munjuk Sempurna is the Contextual learning model with the aim of making students active and critical.The focus of this research is:How is the planning of Islamic Education and Character Building learning through the Contextual learning model in di SDN Munjuk Sempurna in the 2023/2024 Academic Year?How is the implementation of Islamic Education and Character Building learning through the Contextual learning model in di SDN Munjuk Sempurna Academic Year?How is the evaluation of Islamic Education and Character Building learning through the Contextual learning model di SDN Munjuk Sempurna Academic Year?To achieve the research objectives, the researcher used a qualitative research with a case study research design. Data collection techniques in this research used interviews, observation, and documentation studies. Data analysis used the Miles, Huberman, and Saldana data analysis model, namely data condensation, data presentation, and drawing conclusions. In the data validity test, the researcher used source triangulation and technique triangulation.This research found the following conclusions:Learning planning includes four elements, namely:a) The teacher determines the objectives of the Contextual model and the competency objectives.b) The teacher determines the material Prioritizing Honesty and Upholding Justice.c) The teacher determines the Contextual learning model.d) The teacher selects learning resources through books and chooses learning media with PowerPoint and video learning.The implementation of learning is as follows:a) The teacher opens the lesson by giving motivation, appreciation, and reference.b) The teacher delivers the material Prioritizing Honesty and Upholding Justice through PowerPoint media and video learning.